2018
DOI: 10.1038/s41427-018-0078-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation behaviors and mechanisms of MoS2 crystals relevant to bioabsorbable electronics

Abstract: Monolayer molybdenum disulfide (MoS 2 ) exhibits unique semiconducting and bioresorption properties, giving this material enormous potential for electronic/biomedical applications, such as bioabsorbable electronics. In this regard, understanding the degradation performance of monolayer MoS 2 in biofluids allows modulation of the properties and lifetime of related bioabsorbable devices and systems. Herein, the degradation behaviors and mechanisms of monolayer MoS 2 crystals with different misorientation angles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Moreover,i th as been shown that temperature, pH, and the type and concentration of ions could influence the rate of degradation. [28] These resultsconfirm the strong oxidative nature of the intermediates formed during the enzymaticc ycle of hMPO along with hypochloritei ons (HOCl). Moreover,p reviousr eports confirmed that 1T-MoS 2 sheets were much more rapidly degraded or oxidized by hydrogenp eroxidea lone when compared with hMPO/H 2 O 2 treatment, [11] while it took3 0hfor2 H-MoS 2 with hMPO/H 2 O 2 treatment.…”
Section: Mixed Glial Cell Compatibilityand Enzymatic Degradationsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover,i th as been shown that temperature, pH, and the type and concentration of ions could influence the rate of degradation. [28] These resultsconfirm the strong oxidative nature of the intermediates formed during the enzymaticc ycle of hMPO along with hypochloritei ons (HOCl). Moreover,p reviousr eports confirmed that 1T-MoS 2 sheets were much more rapidly degraded or oxidized by hydrogenp eroxidea lone when compared with hMPO/H 2 O 2 treatment, [11] while it took3 0hfor2 H-MoS 2 with hMPO/H 2 O 2 treatment.…”
Section: Mixed Glial Cell Compatibilityand Enzymatic Degradationsupporting
confidence: 62%
“…Usually, over two months are needed to completely degrade and absorb a polycrystalline MoS 2 monolayer of approximately 200 nm size in PBS solution at 37 °C. Moreover, it has been shown that temperature, pH, and the type and concentration of ions could influence the rate of degradation [28] . These results confirm the strong oxidative nature of the intermediates formed during the enzymatic cycle of hMPO along with hypochlorite ions (HOCl).…”
Section: Resultsmentioning
confidence: 69%
“…3a. While the mobility of the device after passivation reserved $71% of its initial value, the bare MoS 2 device loses most of its mobility (3.8% remained) after exposed to air for 10 d due to the degradation induced by dislocations and point defects in MoS 2 [49,50]. Fig.…”
Section: Coxmentioning
confidence: 94%
“…Considering the low electronic density of such materials, such defects will obviously affect their electronic properties, for example by inducing metallic states or modifying the original electronic gap of the material. As a consequence, electronic transport properties or chemical reactivity might be modified [21,22]. On another hand, one can think about exploiting these new induced properties to create new nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%